Film narratology - Verstraten, Peter (University of Toronto Press, 2009)
In Film Narratology, Peter W.J. Verstraten makes film narratives his primary focus, while noting the unexplored and essentially different narrative effects that film can produce with mise-en-scCne, cinematography, and editing.